Determining the stock status of snapper (Lutjanus sp.) using surplus production model: a case study in Banyuasin coastal waters, South Sumatra, Indonesia. (January 2020) - Fauziyah,; Purwiyanto, A I S; Agustriani, F; Putri, W A E; Ermatita,; Putra, A
Abstract: Snapper ( Lutjanus sp.) is an economically important fish for local fishermen in Banyuasin coastal water of South Sumatra. However, the current and historical stock of this species is still unknown. This study was aimed to estimate the stock status of Lutjanus sp. in the Banyuasin coastal waters. The annual catch and effort data were analyzed from 2008 to 2016. The different surplus production models were tested to obtain the best-fitted model based on the sign suitability test, model performance test, and multiple criteria analysis. The results indicated that the best-fitted model for Lutjanus sp. was the Fox model. The model had the best value for the determination coefficient (R 2 = 97.2%), Nash-Sutcliffe Efficiency (-0.277), Mean Absolute Deviation (29.198), Mean Square Error (1, 190.522), Root Mean Square Error (34.504), and RMSE-observations Standard Deviation Ratio (1.13), whereas the value of Mean Absolute Percentage Error (0.05) was the second-best value. The optimum effort (Eopt ), maximum sustainable catch (CMSY ), and total allowable catch were 22.236 trips/year, 623 ton and 498 ton/year, respectively. Based on plotting the effort and exploitation level (141%; 102%) in 2016, the stock status of Lutjanus sp. indicated depleting stock, the high fishing pressure and could encourage overfishing stock in the future.